AUV-based suspended particulate matter (SPM) concentration (mg/L) from a mining trial at GSR contract area in the Clarion Clipperton Zone during the MANGAN 2021 (IP21) expedition - Gazis, Iason-Zois; de Stigter, Henko; Mohrmann, Jochen; Heger, Karl; Greinert, Jens (PANGAEA, 2025)
Bottom water suspended particulate matter (SPM) concentration (mg/L) measured by an autonomous underwater vehicle (AUV) during a mining trial at the GSR contract area in the Clarion Clipperton Zone during the MANGAN 2021 (IP21) expedition. The AUV was equipped with a standalone JFE Advantech Infinity Series ATUD-USB (JFE) mounted on the dorsal fin of the AUV and a WetLabs ECO FLNTU (FLNTU) coupled to a SAIV A/S SD208 6K CTD mounted on the nose of the AUV. The AUV survey pattern and sensor settings are described in Vink et al. (2022). The data processing, calibration (for JFE) and intercalibration (for FLNTU) to SPM concentration are described in Gazis et al. 2025. The Royal Netherlands Institute for Sea Research (NIOZ) provided the JFE sensor in the framework of the JPIO MiningImpact2 project. The Global Sea Minerals Resources (GSR) chartered the AUV with the FLNTU sensor.